2016
DOI: 10.1007/s12124-016-9368-0
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Cultural Intervention: Formation of Inhibitory Collective and children’s Self-Defensive Regulation in a Chinese School

Abstract: A sequel to the previous article "Roots of Excellence: The Releasing Effect of Individual Potentials through Educational Cultural Intervention in a Chinese School" (in press), the present study is on the unexpected reversal phenomena in the process of cultural intervention. The goal of the intervention is to construct the dynamics of Jiti (well-organized collective in Chinese) through creative activities to promote students' development. In the intervention, the releasing effect (Wu et al. 2016) emerged as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The activity centered on telling stories based on pictures provided. Four images were used from prior research (Wu et al, 2017), with these pictures respectively showing (1) students in a class, (2) two kids playing games, (3) a child talking with an adult, and (4) five children standing in a circle. These particular images were chosen because their themes would be familiar to the students and so would likely elicit stories more easily.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity centered on telling stories based on pictures provided. Four images were used from prior research (Wu et al, 2017), with these pictures respectively showing (1) students in a class, (2) two kids playing games, (3) a child talking with an adult, and (4) five children standing in a circle. These particular images were chosen because their themes would be familiar to the students and so would likely elicit stories more easily.…”
Section: Methodsmentioning
confidence: 99%
“…Almost all of their teachers and students come from the countryside but currently live in cities. Additionally, a recent study found that one of the characteristics of migrant schools is their non-comprehensive view toward education—that is, their emphasis on the development of arithmetic and literacy skills while disregarding learning through folklore, games, and activities (Wu et al, 2017). In fact, the students and teachers at the migrant schools are often familiar with such folklore, games, and cultural activities as they are from these traditional cultural backgrounds.…”
Section: Introductionmentioning
confidence: 99%